Optimization of Propane Compressor Capacity and Flow Rate in Refrigeration System - Nurrahman, Arif (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Plant X requires pressurized gas in the refrigeration system unit, which plays an important role in the smooth operation of the production system. This is because propane gas is used as a support for the main operating system in the manufacture of LPG. More precisely as a cooling medium for tools called Chiller and Sub-Cooler. To obtain the pressurized propane gas, a screw compressor type positive displacement compressor is used. Propane Compressor C-440 A has a function, namely to circulate propane gas which is used to cool or lower the temperature of hydrocarbon gas. Considering the important role of the Propane Compressor C-440 A screw compressor, it is necessary to optimize it to determine the performance of the compressor. Optimization steps need to be carried out to find the most effective and efficient operating conditions. By lowering the suction temperature and increasing the rotational speed of the rotor. The reference parameter is that the targeted capacity has increased by 9%, resulting in the actual calculation of 30614.40 cfm and optimization of 30902.03 cfm. The mass flow rate is targeted to increase by 4%, resulting in an actual calculation of 627.92 lbm/min and an optimization of 654.80 lbm/min. With this, it can be calculated that the economic value is 26.89 lbm/min.